A population‐based study of the association between dysglycaemia and hearing loss in middle age. Issue 5 (20th February 2017) - Sommer, J.; Brenann‐Jones, C. G.; Eikelboom, R. H.; Hunter, M.; Davis, W. A.; Atlas, M. D.; Davis, T. M. E.
Abstract: Aims: To investigate the independent associations between hearing loss and dysglycaemia in a sample of middle‐aged adults, including separate analysis of those aged < 60 years. Methods: The first 2023 participants in the cross‐sectional Busselton Health Ageing Survey were assessed for hearing loss ≥ 26 dB (better ear) for four‐frequency average (4FA) of pure‐tone thresholds at 500, 1000, 2000 and 4000 Hz, and high‐frequency average (HFA) of pure‐tone thresholds at 4000 and 8000 Hz. Results: Valid data from 1864 participants in the Busselton Health Ageing Survey [92.1%; mean ±sd age 56.2 ± 5.5 years, 46.0% men, 120 (7.0%) with diabetes, 274 (14.7%) with prediabetes] were analysed, of whom 103 (5.5%) had four‐frequency average hearing loss and 561 (30.1%) had high‐frequency average hearing loss. In multivariable analyses, glycaemic status was not independently associated with four‐frequency or high‐frequency average hearing loss. In the 1286 participants aged < 60 years, there was no relationship between dysglycaemia and high‐frequency average hearing loss, but the prevalence of four‐frequency average hearing loss increased from 2.3% (95% CI 1.5–3.4) in participants with normoglycaemia to 5.7% (95% CI 3.0–10.6) in those with prediabetes and 10.2% (4.2–21.5) in those with diabetes (trend P = 0.003). In multivariable analysis with normoglycaemia as reference, the odds ratios for four‐frequency average hearing loss were 2.84 (95% CI 1.29–6.27) for prediabetes and 5.93 (95% CI 1.67–21.05) for diabetes ( P ≤ 0.01) in the < 60 year age group. Conclusions: There was progressively increasing mid‐range hearing loss with worsening glucose tolerance in younger individuals, suggesting dysglycaemia‐associated early‐onset presbycusis. What's new?: There have been few population‐based studies of hearing loss in diabetes in well characterized participants, and none in prediabetes. In participants in the Busselton Health Ageing Survey aged < 60 years, increasing dysglycaemia was associated with increasing mid‐range hearing loss after adjustment for other recognized risk factors for hearing impairment There was no relationship between dysglycaemia and hearing loss in participants aged ≥ 60 years. Abnormal glucose tolerance may independently accelerate the onset of presbycusis in younger people with diabetes.